Protective Effect of Obeticholic Acid on Sepsis-Induced Liver Dysfunction via Regulating Bile Acid Homeostasis - Jiahui Wang; Li Ma; Yuan An; Yan Ge; Dan Xu; Enqiang Mao (Pharmaceuticals)
Background/Objectives: Abnormal bile acid (BA) pool may play an important role in inducing liver damage in sepsis. Farnesoid X receptor (FXR) is a main negative feedback regulator of BA metabolism. This study aims to explore the protective effect and mechanism of the FXR agonist obeticholic acid (OCA) on liver dysfunction when sepsis occurs. Methods: A rat model of sepsis was induced by cecal ligation and puncture (CLP) for 24 h. Systematic inflammation, tissue injury, hepatic FXR, and BA transporter expression were investigated in the CLP rats and sham-operated control rats with and without OCA pre-treatment (10 mg/kg, gavage) at 2 h before operation. Liquid chromatography–tandem mass spectrometry (LC-MS/MS) assay was performed to access BA composition in the rats’ serum and livers. The injury and inflammatory effects of the elevated unconjugated BAs found in the CLP rats was further verified in a hepatic cell line BRL-3A in vitro. Results: Hepatic FXR was repressed in CLP rats, whereas OCA upregulated liver FXR and hepatic BA transporter expression, reduced total serum BA concentration, ameliorated the elevation of serum levels of IL-1β and IL-6, and improved liver and ileal tissue injuries. OCA administration reduced the elevated unconjugated BAs in both serum and liver, and effectively inhibited increases in cholic acid (CA), deoxycholic acid (DCA), and 7-ketoDCA concentrations in CLP rat livers. These BA fractions promoted the release of aspartate aminotransferase (AST) from BRL-3A cells and increased IL-6, CXCL2, and monocyte chemoattractant protein-1 (MCP-1) expression in the cells, along with enhanced transcription factor nuclear factor-κB activation. Conclusions: Liver inflammation and dysfunction during sepsis is attributable to significant changes in bile acid composition in the blood and liver. FXR activation reduces systemic inflammation and liver dysfunction by regulating bile acid homeostasis, especially inflammatory unconjugated bile acid components.